O coordenador pedagógico como formador de professores em grupos heterogêneos na escola: as ações de formação e suas implicações - Bonafé, Elisa Moreira (2015)
This study aims to identify the strategies used in teacher training in schools that make teachers improve their classroom practices with students. From interviews with four pedagogical coordinators of public schools from São Paulo city, it was possible to observe the diversity of challenges that are reflected in the planning and the implementing of continuous learning of teachers. It was also identified that there is a lack of clarity for coordinators about the potential actions they can perform with teachers at school and how these actions can be performed, especially regarding to the conduction of the actions of training and their strategies. Using as reference the studies of Imbernón, it was produced some reflections in favor of training in the work context due to the fact that it considers the real situations that arise in the school routine. Placco, Almeida and Souza collaborated with studies and contributions to the routine of the pedagogical coordinators, the needs and the possibilities of change in their formative function. At the end, it is presented a proposal for pedagogical coordinators that suggest the theoretical study in the continuing training of teachers and, moreover, it is suggested practical experience that can also motivate change in professional performance of the pedagogical coordinators themselves. It is expected that, with continuous teacher training, the pedagogical coordinators professionalize their activities in the schools concerning the learning and the observation of teachers and consequently, they can propose consistent and efficient solutions for the school difficulties and develop actions to encourage change in the pedagogical practices of teachers